On the way to QMS implementation: the main milestones and issues in emerging economy - Lebedynets, V.; Prokhorenko, Olena; Brin, P. V.; Nehme, M. N. (My University, 2022)
The aim of the research is to analyze typical problems in the implementation of quality management systems (QMS) on the basis of private production enterprises which operate in emerging economy context and to develop a rational strategic plan for the design and implementation of such a system, taking into account the experience of successful organizations. The main benefits of implementing QMS are presented. In the article it is recommended to consider the formation of QMS as a project with the appropriate stages of activities. The following positions are envisaged at the initiation stage: formalization of the decision on QMS implementation, appointment of project participants, project team training, as well as development of mission, vision, quality policy and QMS process structure. At the implementation stage, it is proposed to develop and approve QMS documents, as well as to implement an internal audit program. At the stage of project closure, it is advisable to put into operation the developed system and pass a certification audit in order to obtain a certificate of compliance with the requirements of ISO 9001. The article presents the structure, content, sequence and estimated duration of all the stages of the project, as well as the division of responsibilities between the project team members. Emphasis is placed on the main issues which can arise at different stages of such a project. In the paper the following range of issues was identified: inconsistency of QMS processes structure with the existing organizational structure of the enterprise; incorrect definition of the performance indicators for processes at different hierarchy levels; erroneous decisions in the internal documentation system organizing. In its turn, in the article the causes for the above-mentioned issues were identified, namely: insufficient motivation of project participants, lack of time or other necessary resources, unwillingness to change the current management system of the company, inconsistency of real goals with the stated ones, etc. In the article it is proposed to divide the main causes of issues into three basic groups: by project participants (personal), bureaucratic (systemic) and leadership (administrative). The authors propose a number of measures to minimize the risks of issues in the QMS implementation, and determine the distribution of areas of responsibility for these measures organizing.
Keywords: quality management system; ISO 9001 standard; critical success factors; corporative strategy